Membangun Fondasi Pendidikan : Solusi Atas Minimnya Kemampuan Membaca dan Berhitung di Sekolah Dasar Indonesia - Nafisah Qotrotun Nadda (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Reading and numeracy skills are the main foundations for the learning process, cognitive development, and student success in everyday life. However, in Indonesia, these two basic skills remain a serious challenge, particularly at the elementary school level. Based on the results of the 2023 National Assessment, 61.53% of students have not achieved minimum competency in reading literacy, and 46.67% have not met basic standards in numeracy. This condition reflects a significant gap between curriculum targets and actual achievements in the field. This low achievement is influenced by various factors, including uneven teacher quality and competence, limited educational infrastructure such as inadequate libraries, limited internet access, especially in remote areas, and disparities in literacy development between regions. This study uses a descriptive qualitative approach with a literature review method and analysis of empirical data from various sources, including government reports, national survey results, and previous research, to identify the root causes and formulate improvement strategies. The study results indicate that strengthening the foundations of basic education must be done through improving teacher competency, ongoing training, and updating teaching methods to be more contextual. The use of educational technology and digital media can be an innovative solution to expand access to quality learning, especially in areas with limited facilities. Furthermore, revitalizing school and community libraries, as well as strengthening community-based literacy programs, is considered capable of fostering a culture of reading and numeracy from an early age. With a comprehensive approach, collaboration between the government, schools, communities, and the private sector can create an inclusive, responsive, and sustainable education ecosystem. This joint effort is expected to reduce the literacy and numeracy achievement gap, while preparing a young generation that is capable, critical, and adaptive to future challenges.